PENGARUH PROFESIONALISME, KUALITAS AUDIT, DAN PENGALAMAN AUDITOR TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS DALAM LAPORAN KEUANGAN - Sholikhah, Mar’atus; Sari, Mulya; Izzah, Anisatul; Rokhman, M Taufiq Noor (Magister Manajemen Universitas Wisnuwardhana, 2018)
The purpose of this study is first, providing empirical evidence of the effect of Auditor Professionalism on Materiality Level Considerations. Second, provide empirical evidence of the effect of audit quality on materiality level considerations. Third, provide empirical evidence of the Effects of Auditor Experience on Materiality Level Considerations. This study uses a quantitative approach with research respondents, namely auditors who work in public acconting office in Malang city. Data collection techniques using questionnarie instruments. The analytical tool used is multiple regression. The results of the study show that: 1) Auditor Professionalism (X1) has a significant effect on the Materiality Level Consideration, which is indicated by the sig value of 0.002; 2) Audit Quality (X2) has a significant influence on Level Considerations Materiality, which is indicated by a sig value of 0.026; 3) and Experience Auditors (X3) have a significant influence on consideration Materiality level, which is indicated by the sig value of 0.047. Keywords: Professionalism, Audit Quality, Auditor Experience, Materiality Level, Financial Report